THE INFLUENCE OF PRODUCT AVAILABILITY, PACKAGING AND LABELS ON RICE PURCHASING DECISIONS AT PT AROMA NUSAJAYA KARYA IN BATAM - Stanley, Stanley; Wasiman, Wasiman (Universitas Muhammadiyah Tangerang, 2024)
In a competitive industry such as the food industry, understanding the factors influencing purchasing decisions can provide a competitive advantage. The purpose of this study was to explore the impact of product availability, packaging, and labels on the decision-making process of rice consumers at PT Aroma Nusajaya Karya in Batam. The population is 319 people. Using the Slovin formula, a sample of 178 respondents was determined. The analytical approach used in this study involved multiple linear regression. The results obtained from multiple linear regression analysis showed that product availability had a major effect of 43.8% on consumer purchasing decisions. Similarly, packaging had a significant impact of 25.6%, while labels contributed a significant 15.8% to the decision-making process. The results of the t test and F test that the availability of products, packaging, and labels, both individually and collectively, have a significant influence on rice purchasing decisions at PT Aroma Nusajaya Karya in Batam. By using this research to improve marketing strategies, PT Aroma Nusajaya Karya can become more competitive in the market.